An assessment method for dermal structures using cross‐polarized light imaging with a green light‐emitting diode. Issue 6 (25th June 2020) - Hong, Ji Hyuck; Park, Sung Jin; Ham, Min Seok; Kim, Dai Hyun; Rhyu, Im Joo; Kye, Young Chul; Ahn, Hyo Hyun
Abstract: Background: Several experimental methods for evaluating dermal structures exist; however, most of these are not used in dermatology clinics because of cost and functional limitations. Objective: To propose a simple, non‐invasive method for dermal structure evaluation using a green light‐emitting diode (LED) with cross‐polarized light (CPL) imaging and compare the quality of the images taken using either green or white LED. Materials and Methods: Skin specimens were taken from fifteen cadavers. Images were captured using CPL photography with a green or white LED. The Commission International d'Eclairage L * a * b * (CIELAB) values were calculated for each image. The skin specimens were processed and stained with Masson's trichrome to visualize collagen fibers with major image scattering. The images were histologically analyzed, and correlational and regression analyses were performed to determine the relationship between the L * values and histologic measurements. Results: The L * values for the green images were positively correlated with collagen fiber density, reticular collagen bundle diameter, and dermal thickness. They were effective for estimating dermal properties. The L * values for the white images were positively correlated with reticular collagen bundle diameter and dermal thickness. Correlational coefficients for white images were lower than those for green images. In regression analysis, green images showed a higher coefficient of determination ( R 2 ) for predicting reticular collagen bundle diameter than white images (0.1128 vs. 0.0827). Conclusion: Cross‐polarized light imaging with a green LED is a simple, non‐invasive method for evaluating dermal structures. The use of a green LED was also more effective for image analysis.